To simplify the expression \( 2(2z + 4) - 2(3z + 10) \) using the Distributive Property, follow these steps:
-
Distribute \( 2 \) in \( 2(2z + 4) \): \[ 2 \cdot 2z + 2 \cdot 4 = 4z + 8 \]
-
Distribute \( -2 \) in \( -2(3z + 10) \): \[ -2 \cdot 3z - 2 \cdot 10 = -6z - 20 \]
-
Combine the results: \[ 4z + 8 - 6z - 20 \]
-
Combine like terms:
- For the \( z \) terms: \( 4z - 6z = -2z \)
- For the constant terms: \( 8 - 20 = -12 \)
-
The simplified expression is: \[ -2z - 12 \]
Therefore, the final answer is Negative 2z minus 12.